The Significance of Enjoining What is Right and Warning Against What is Wrong - Isa, Yakubu (International Journal of Humanities, Education, and Social Sciences, 2024)
Islam was built with the mission to enjoin what is right and want against what is wrong, so that the mankind problems will be drastically solved. The objective of this paper was to identify significance of calling people to right things and warning against wrong doings. A Muslim is by his right enjoined to do the right and exhort others. For him to be able to achieve this great objective he has to be behaving well according to tenets and etiquettes of Islam. Major things to call people to are: Taqwa (conscious to God), brotherhood among Muslims, commanding the right thing, believe in Qadr, believe in Angels, believe in unity of Almighty Allah, believe in Prophets, and believe in Hereafter among others.